Perceptions of Certified EFL Teachers Pertaining to Teacher Certification Program in Central Sulawesi, Indonesia - Syafar, Anshari (Journal of Educational Sciences, 2018)
The state and condition of Indonesian teachers have graduallychanged to a better nuance due to the compensation of teacher certificationprogram (TCP). The program has conceivably raised the status of theteachers in social and economic lives. However, the impact of the programon the improvement of overall teacher‘s quality—teaching performance asmandated by Teacher and Lecturer Law remains questionable, and the bigquestion is what and how teachers perceive and act in response to theobjective of the program. The program aims not only to increase theteachers‘ salary, but also to improve the quality of their teachingperformance based on the teacher standard competence, that is pedagogical,personality, social, and professional competences. Therefore, the studyexplore and describe certified EFL teachers‘ perceptions concerning benefitsof the program on thier social and economic lives, improvement and qualityof their teaching practices; perceptions on the ways management ran theprogram; and expectations for better services of the TCP management.